2004
DOI: 10.1111/j.0013-9580.2004.66303.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Growth and Endocrinal Disorders during Pubertal Maturation in Girls with Epilepsy

Abstract: Summary:Purpose: This study investigated the effect of epilepsy and/or antiepileptic drugs (AEDs) on the physical growth, pubertal development, and androgenic status of girls with epilepsy between ages 8 and 18 years.Methods: Sixty-six female patients with epilepsy, their mean ages 13.47 ± 3.5 years, were included. Anthropometric measurements, staging of pubertal maturation, and clinical manifestations of hyperandrogenism were assessed, as well as measurement of serum levels of testosterone, dehydroepiandroste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 53 publications
4
26
0
8
Order By: Relevance
“…These results are compatible with earlier reports of normal height in girls treated with VPA [12,33] and boys treated with diverse antiepileptic drugs for a mean of 3.1 years [33]. By contrast, others reported negative effects of various antiepileptic drugs on height in male adolescents >16 years, regardless of treatment duration [5]. However, the cohort of the latter cross-sectional study was heterogeneous and included patients treated with polytherapy as well as patients with symptomatic epilepsy, and the assessment of shorter height was based on a comparison to healthy age-matched controls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are compatible with earlier reports of normal height in girls treated with VPA [12,33] and boys treated with diverse antiepileptic drugs for a mean of 3.1 years [33]. By contrast, others reported negative effects of various antiepileptic drugs on height in male adolescents >16 years, regardless of treatment duration [5]. However, the cohort of the latter cross-sectional study was heterogeneous and included patients treated with polytherapy as well as patients with symptomatic epilepsy, and the assessment of shorter height was based on a comparison to healthy age-matched controls.…”
Section: Discussionsupporting
confidence: 91%
“…It has been associated with an increased frequency of reproductive endocrine disorders in females [2] and abnormal growth and pubertal development in children [3,4,5]. The pathogenic mechanisms underlying the endocrine disorders may be related to impaired hypothalamic regulation of the pituitary by epileptic discharges in the medial temporal lobe [6,7,8] and/or antiepileptic drugs [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The increase in body weight appears to occur most frequently in post-pubertal girls taking VPA [3, 4, 6, 8, 9, 12, 15, 17, 19, 20,25,26,27], although VPA-induced weight gain has also been reported also in pre-pubertal patients [4,5,6,7, 10, 24, 26, 28]. Finally, a recent population-based study reported that increase in body weight is more common in patients treated with VPA during puberty if epilepsy and medication continue into adulthood [16].…”
Section: Valproate and Weight Gainmentioning
confidence: 99%
“…8 In epi lep tic children, obe sity 12 growth re tar da ti on, hype ran dro genism and polyc ystic ovary syndro me may oc cur du ring the an ti e pi lep tic tre at ment co ur se. 13 The kid ney is ra rely in vol ved, wa ter re ten ti on du e to inap prop ri a te sec re ti on of an ti di u re tic hor mon being the most fre qu ent ad verse re ac ti on. Acu te re nal fa i lu re may appear been related as an ad vers re acti on to CBZ, mostly as a tu bu lo in ters ti ti al nep hri -Özsaraç ve ark.…”
Section: Discussionmentioning
confidence: 99%